Post-Covid-19 Shifts: Analysing Changes in Bangladeshi Undergraduate Students' Attitudes Toward Face-to-Face Learning (European Journal of Teaching and Education, 2025)
This study explores shifts in undergraduate students' attitudes toward face-to-face classes after returning to in-person education following the COVID-19 pandemic. The pandemic necessitated a shift to online learning, requiring students to adapt to remote instruction. With the resumption of in-person classes, students faced new psychological and behavioral challenges, influencing their engagement and perceptions. Using a qualitative approach, the study examined 48 English department students at a government college in Bangladesh. Data were collected through open-ended questions via Google Forms and analyzed using inductive thematic analysis based on the Tripartite Model of Attitude. Findings reveal significant changes in students' feelings, beliefs, and behaviors regarding face-to-face instruction. While students valued in-person classes both before and after the pandemic, a growing number questioned their mandatory nature, highlighting the flexibility of online alternatives. Many continued to view face-to-face classes as effective but sought a balance between traditional and online modes of learning. Behaviorally, students increasingly prioritized social and teacher interactions over mere academic attendance. These findings emphasize the need for institutions to adopt flexible, hybrid learning models that address evolving student preferences. Educators should integrate active learning strategies and foster supportive environments to sustain engagement and capitalize on the strengths of both face-to-face and online instruction.